The Relationship Between Internal Communication, Work Motivation, and Employee Performance at Bank OCBC NISP Jakarta, Pluit Karang Utara Branch - Romarta Agustina; Christina Natalina; Jonny Siagian (Universitas Kristen Indonesia, 2023)
This study aims to determine the relationship between Internal Communication and Work Motivation, to employee performance at Bank OCBC NISP Jakarta, Pluit Karang Utara branch. The sample was determined as many as 40 respondents consisting of tellers, customer service, marketing, operators and branch heads. Researchers used saturated sampling techniques that include internal communication variables, work motivation, and employee performance. The analysis method used is a descriptive analysis of respondents, the data description includes correlation test analysis, while the correlation test used is a spearman rank correlation test. The results of this study show that there is a significant relationship between internal communication and employee performance which is shown with a significance value of 0.000 < 0.05 and there is a significant relationship between work motivation and employee performance, which is shown with a significance value of 0.000 < 0.05. Keywords: Internal Communication, Work Motivation, Employee Performance